Legal Mechanism For Regulation Of Trade Relations Of The Republic Of Uzbekistan Within The Framework Of Joining The World Trade Organization - Oybek Yakubov (Periodica Journal, 2023)
This scientific article notes the formation of the state as a full-fledged participant in international trade relations, the development of partnership trade relations, as well as joining leading international trade organizations to enter the international market. Also, this paper discusses the identification of possible problems and prospects for the membership of the Republic of Uzbekistan in the World Trade Organization, the characteristics of the socio-economic situation of the country, the prospects for the development of the current state of the country, the assessment of the foreign economic activity of the state, the benefits and risks for the Republic of Uzbekistan when joining the WTO
Keywords: legislative regulations; legal mechanism; accession to the WTO